Added Value of Arterial Spin Labeling in Detecting Posterior Reversible Encephalopathy Syndrome as a Stroke Mimic on Baseline Neuroimaging: A Single Center Experience - Weinstein, Joseph D.; Hamam, Omar; Urrutia, Victor C.; Lu, Hanzhang; Luna, Licia P.; Tekes-Brady, Aylin; Bahouth, Mona; Yedavalli, Vivek (Frontiers in Neurology, 2022)
Differentiating stroke from stroke mimics is a diagnostic challenge in every day practice. Posterior Reversible Encephalopathy Syndrome (PRES) is an important stroke mimic with nonspecific symptomatology, making prompt and accurate diagnosis challenging. Baseline neuroimaging plays a pivotal role in detection and differentiation of stroke from many common mimics and is thus critical in guiding appropriate management. In particular, MR perfusion (MRP) imaging modalities provide added value through detection and quantification of multiple physiological parameters. Arterial Spin Labeling (ASL) is a non-contrast, noninvasive MRP technique increasingly used in clinical practice; however, there is limited description of ASL in PRES in the existing literature to date. In this single center retrospective pilot study, we find that ASL can potentially offer added value to structural imaging and clinical presentation in increasing confidence in diagnosing PRES.